Graphitic carbon nitride encapsulated sonochemically synthesized β-nickel hydroxide nanocomposites for electrocatalytic hydrogen generation. (8th December 2022) - Devi, S. Brindha; Sekar, Sankar; Kowsuki, K.; Maiyalagan, T.; Preethi, V.; Nirmala, R.; Lee, Sejoon; Navamathavan, R.
Abstract: Hydrogen evolution reaction (HER) carried out from electrocatalysis of water splitting is playing a major role in the production of green and clean hydrogen. In this paper, we report on the synthesis of graphitic carbon nitride on nickel hydroxide (g-C3 N4 /Ni(OH)2 ) nanocomposites by a simple ultrasonication method. The characterizations include the XRD, Raman, FESEM and electrochemical studies to analyze the performance of the as developed material over hydrogen evolution reaction. The morphological analysis shows that the aggregated interconnected g-C3 N4 /Ni(OH)2 (GCN/NH) nanocomposites with an average particle size of ∼20 nm. These GCN/NH nanocomposites exhibit the lowest overpotential of 341 mV at 10 mA/cm 2 which is smaller than that of the pristine Ni(OH)2 nanosheets at 367 mV. Further, the Tafel slope for GCN/NH nanocomposites reveals a lower value of 131 mV/dec. As a result, g-C3 N4 decorated sheet-like β-Ni(OH)2 exhibits the potential hydrogen evolution in alkaline KOH solution. Excitingly, the as developed hybrid β-Ni(OH)2 nanocomposites show superior electrocatalytic behaviour during the hydrogen evolution reaction and also improve the catalytic stability than pure nanosheets. From these observations, one can say that this g-C3 N4 /Ni(OH)2 nanocomposite electrocatalyst can play a splendid role in future energy technology. Highlights: One step synthesis of β-Ni(OH)2 and g-C3 N4 /Ni(OH)2 via sonochemical method. Prepared electrodes were characterized for the electrocatalytic HER studies. The electrochemically active surface area of nanocomposite is higher than that of the pristine. The overpotential of the g-C3 N4 /Ni(OH)2 nanocomposite is lower than that of the pristine Ni(OH)2 .